2001
DOI: 10.1038/88432
|View full text |Cite
|
Sign up to set email alerts
|

Kainate receptor-mediated heterosynaptic facilitation in the amygdala

Abstract: Prolonged low-frequency stimulation of excitatory afferents to basolateral amygdala neurons results in enduring enhancement of excitatory synaptic responses. The induction of this form of synaptic plasticity is eliminated by selective antagonists of GluR5 kainate receptors and can be mimicked by the GluR5 agonist ATPA. Kainate receptor-mediated synaptic facilitation generalizes to include inactive afferent synapses on the target neurons, and therefore contrasts with other types of activity-dependent enduring s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
104
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(117 citation statements)
references
References 45 publications
11
104
1
1
Order By: Relevance
“…fEPSPs baseline was recorded for 10 minutes and ATPA was applied for 15 minutes. During the 15 minute ATPA application, the amplitude and slope of fEPSPs decreased below baseline, similar to that seen in other laboratories (Li et al, 2001). fEPSP amplitude and slope rapidly (in <5 min) returned to baseline levels after removing ATPA from the slice.…”
Section: Acute Ethanol and Ubp 296 Block Atpa Induced Synaptic Plastisupporting
confidence: 87%
See 4 more Smart Citations
“…fEPSPs baseline was recorded for 10 minutes and ATPA was applied for 15 minutes. During the 15 minute ATPA application, the amplitude and slope of fEPSPs decreased below baseline, similar to that seen in other laboratories (Li et al, 2001). fEPSP amplitude and slope rapidly (in <5 min) returned to baseline levels after removing ATPA from the slice.…”
Section: Acute Ethanol and Ubp 296 Block Atpa Induced Synaptic Plastisupporting
confidence: 87%
“…Previous studies have reported that KA EPSCs can be recorded by stimulation of the external capsule and the amplitude of these responses can be markedly enhanced by using short stimulus trains (Li et al, 2001;Li and Rogawski, 1998). Therefore, in our first experiments, KA EPSCs were evoked in BLA neurons by stimulus trains delivered to the external capsule (Fig.…”
Section: Acute Ethanol Dose Dependently Decreased Ka Mediated Epscsmentioning
confidence: 78%
See 3 more Smart Citations